Building Inclusive Collaboration: The Impact of Sourcing Channel and Gender on Employee Performance Through Right Placement - Tatasari, Titis (LPPPIPublishing, 2024)
This research analyzes how Recruitment Channel and Gender affect Employee Performance with Placement as an intervening variable. This study used a quantitative method design with 34 saturated samples taken from PT. SJI Surabaya, Indonesia. The data collection in this study was primary data, and the instrument used was a self-administered questionnaire addressed to 34 respondents of PT SJI Surabaya, Indonesia, consisting of 4 variables, namely recruitment channel, gender, placement, and employee performance. Data analyses used SEM SmartPLS-3. The results indicate that gender is not a direct determinant of employees' performance, but it affects placement considerably. Placement influences performance significantly and thus might be an intervening variable in the performance-gender relationship. Recruitment channels do not significantly influence either employee performance or placement. Strong points of this study include the application of Organizational Psychology theory to understand the relation of variables, thus giving a sound conceptual framework in the context of the Indonesian Industry. This is a study that will try to provide insight for companies in managing gender diversity and the recruitment process. Results from the present study have highlighted placement into jobs, which should take into consideration the individual characteristics and demands of a particular job and vice versa, while implementing diversity and inclusion management will create a favorable working environment that actually enhances employee performance.